Analysis of Carbohydrates from the Seeds of Centratherum anthelminticum Kuntze - Yadava, R.N.; Barsainya, Deepak (Asian Journal of Chemistry, 2010)
In the present note we reported our results on the analysis of carbohydrates from the seeds of Centratherum anthelminticum kuntze.